The Pros and Cons of Problem-Based Learning from the Teacher’s Standpoint - Ribeiro, Luis Roberto (Journal of University Teaching and Learning Practice, 2011)
This article focuses on a teacher’s evaluation of an experiment with problem-based learning (PBL) and its effects on his professional development. This case study, of a descriptive-analytical nature, involved the collaboration between the researcher and teacher in the planning, implementation of PBL and, to some extent, analysis of results. Research data—collected via participant observation of classes and open-ended interviews with the teacher—were analyzed in light of the literature on PBL, teacher knowledge base, and professional development. Results indicate teacher satisfaction, but also point to higher class unpredictability and increased time/workload. PBL also seems to distribute teaching workload more evenly throughout the semester than traditional methods do. This hinders routinisation and constrains teachers’ autonomy. On the other hand PBL appeared to foster the teacher’s development of his teaching knowledge base, especially regarding the knowledge of students, their reasoning mode and interests.